Multicenter prospective evaluation of diagnostic potential of flow cytometric aberrancies in myelodysplastic syndromes by the ELN iMDS flow working group. Issue 1 (23rd November 2022) - Kern, Wolfgang; Westers, Theresia M.; Bellos, Frauke; Bene, Marie Christine; Bettelheim, Peter; Brodersen, Lisa Eidenschink; Burbury, Kate; Chu, Sung‐Chao; Cullen, Matthew; Porta, Matteo Della; Dunlop, Alan Stewart; Johansson, Ulrika; et al.
Abstract: Background: Myelodysplastic syndromes (MDS) represent a diagnostic challenge. This prospective multicenter study was conducted to evaluate pre‐defined flow cytometric markers in the diagnostic work‐up of MDS and chronic myelomonocytic leukemia (CMML). Methods: Thousand six hundred and eighty‐two patients with suspected MDS/CMML were analyzed by both cytomorphology according to WHO 2016 criteria and flow cytometry according to ELN recommendations. Flow cytometric readout was categorized 'non‐MDS' (i.e. no signs of MDS/CMML and limited signs of MDS/CMML) and 'in agreement with MDS' (i.e., in agreement with MDS/CMML). Results: Flow cytometric readout categorized 60% of patients in agreement with MDS, 28% showed limited signs of MDS and 12% had no signs of MDS. In 81% of cases flow cytometric readouts and cytomorphologic diagnosis correlated. For high‐risk MDS, the level of concordance was 92%. A total of 17 immunophenotypic aberrancies were found independently related to MDS/CMML in ≥1 of the subgroups of low‐risk MDS, high‐risk MDS, CMML. A cut‐off of ≥3 of these aberrancies resulted in 80% agreement with cytomorphology (20% cases concordantly negative, 60% positive). Moreover, >3% myeloid progenitor cells were significantly associated with MDS (286/293 such cases, 98%). Conclusion: Data from this prospective multicenter study led to recognition of 17 immunophenotypic markers allowing to identify cases 'in agreement with MDS'. Moreover, data emphasizes the clinical utility of immunophenotyping in MDS diagnostics, given the high concordance between cytomorphology and the flow cytometric readout. Results from the current study challenge the application of the cytomorphologically defined cut‐off of 5% blasts for flow cytometry and rather suggest a 3% cut‐off for the latter.